Enhancing EFL Speaking with Simple Tech: A Junior High Experiment Using Audio-Visual Slides - Yanartik, Nur Rochmah; Mandarani, Vidya (Borneo Educational Journal (Borju), 2025)
This study aims to explore the effectiveness of audio-visual slides in enhancing the speaking skills of seventh-grade students. Despite being a key skill for expressing ideas and interacting in English, speaking is often under practiced in the classroom. To bridge this gap, the study implements audio-visual slides that integrate visual and audio elements to capture students’ attention and stimulate their imagination. The research employs a pre-experimental one-shot case study design involving 32 students. It focuses on four core indicators of speaking proficiency: fluency, pronunciation, grammar, and comprehension. The results show that the students achieved an average speaking score of 69.53, and the t-test value reached 70, indicating their performance in the “good” category, particularly in grammar and pronunciation. These findings indicate that using audio-visual slides positively impacts students’ speaking abilities. Statistical analysis further supports the conclusion that this method is effective. These outcomes highlight that incorporating audio-visual materials into English lessons can create a more dynamic, engaging, and encouraging language learning environment, helping students build greater confidence and competence in speaking English.